Evaluation of Environmental Risk from Heavy Metals in Sediments in Port Areas - Yusrizal; Nuryasin Abdillah; Andri Hendrizal (Postgraduate, University of Mataram, 2024)
This research aims to evaluate the concentration and distribution of heavy metals in sediment in the Port area of ​​PT Pelindo Dumai Branch, which is one of the main ports in Riau Province, Indonesia. Heavy metals such as cadmium, copper, lead, mercury and zinc are known to have significant toxic effects on maritime ecosystems and can accumulate in the food chain, potentially endangering aquatic life and human health. The research methodology involves taking sediment samples from various points around the port area, which are then analyzed using spectroscopic techniques to determine heavy metal concentrations. The results showed that the concentration of heavy metals in sediments varied, with zinc having the highest concentration (average 0.019724 mg/L), followed by copper, lead, cadmium, and mercury. This variation indicates the existence of diverse sources of pollution and uneven distribution in the port area. Although cadmium and mercury concentrations are relatively low, they still raise concerns due to their high toxicity and potential accumulation in the food chain. These results emphasize the need for more intensive environmental monitoring and targeted risk management to reduce the negative impacts of heavy metals on maritime ecosystems and human health. This research provides an important scientific basis for mitigation efforts in port areas, which are crucial to ensuring the sustainability of ecosystems and the well-being of communities that depend on marine resources.